Role of the endothelial cell glycocalyx in sepsis-induced acute kidney injury - Yixun Wang; Yixun Wang; Yixun Wang; Zhaohui Zhang; Zhaohui Zhang; Zhaohui Zhang; Xingguang Qu; Xingguang Qu; Xingguang Qu; Gaosheng Zhou; Gaosheng Zhou; Gaosheng Zhou (Frontiers in Medicine)
Sepsis-induced acute kidney injury (S-AKI) is a common complication of sepsis. It occurs at high incidence and is associated with a high level of mortality in the intensive care unit (ICU). The pathophysiologic mechanisms underlying S-AKI are complex, and include renal vascular endothelial cell dysfunction. The endothelial glycocalyx (EG) is a polysaccharide/protein complex located on the cell membrane at the luminal surface of vascular endothelial cells that has anti-inflammatory, anti-thrombotic, and endothelial protective effects. Recent studies have shown that glycocalyx damage plays a causal role in S-AKI progression. In this review, we first describe the structure, location, and basic function of the EG. Second, we analyze the underlying mechanisms of EG degradation in sepsis and S-AKI. Finally, we provide a summary of the potential therapeutic strategies that target the EG.